2022
DOI: 10.1159/000529057
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Approach to Identifying Individuals with Salt Sensitivity of Blood Pressure

Abstract: Background: Salt sensitivity of blood pressure (SSBP) is a trait observed in both humans and animals, characterized by an increase in blood pressure (BP) following salt loading or a drop in BP following salt depletion. Summary: This “intermediate” phenotype has been reported in a sizable portion of individuals regardless of their hypertensive status; hypertensives (27-51%), normotensives (18-47%). Further, in epidemiological studies, this phenotype is associated with increased adverse cardiovascular outcomes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…We documented that as much as 60% of hypertensives and 47% of normotensives have SSBP depending on the population studied. 12 Women have more SSBP than men, those of African ancestry more than White participants, and older versus younger individuals. 8,9,17 While not all studies reported similar findings, usually, the effect of biological sex was consistent.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We documented that as much as 60% of hypertensives and 47% of normotensives have SSBP depending on the population studied. 12 Women have more SSBP than men, those of African ancestry more than White participants, and older versus younger individuals. 8,9,17 While not all studies reported similar findings, usually, the effect of biological sex was consistent.…”
Section: Discussionmentioning
confidence: 96%
“…We assessed the role of STRN gene variants in women and men from the HyperPATH cohort. Details have been previously reported 5,8,[10][11][12][13] and are provided in Supplemental Material.…”
Section: Methods International Hypertension Pathotype Study Design An...mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, there is no agreement on the measurement of SSBP in the clinic. In general, two common methods have been used in clinical studies 35,40 . The first is to measure the response of BP to low and high dietary salt intake over 1−2 weeks, which is believed to be more clinically relevant and considered the gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the evaluation of salt sensitivity was performed by the modified Sullivan's acute oral saline load and diuresis shrinkage test (MSAOSL-DST), which has been previously used in a Chinese population for epidemiological investigations. [26][27][28] The details of MSAOSL-DST are as follows (Figure 1): each patient took an oral administration of 1000 mL of 0.9% saline solution within 30 min followed by 40…”
Section: Assessment Of Salt Sensitivitymentioning
confidence: 99%